Graphene Oxide-Gold Nanorods Nanocomposite-Porphyrin Conjugate as Promising Tool for Cancer Phototherapy Performance - Thabang Calvin Lebepe; Sundararajan Parani; Vuyelwa Ncapayi; Rodney Maluleke; Grace It Mwad Mbaz; Olufunto Tolulope Fanoro; Jose Rajendran Varghese; Atsuki Komiya; Tetsuya Kodama; Oluwatobi Samuel Oluwafemi (MDPI AG, 2021)
The cancer mortality rate has increased, and conventional cancer treatments are known for having many side effects. Therefore, it is imperative to find a new therapeutic agent or modify the existing therapeutic agents for better performance and efficiency. Herein, a synergetic phototherapeutic agent based on a combination of photothermal and photodynamic therapy is proposed. The phototherapeutic agent consists of water-soluble cationic porphyrin (5,10,15,20-tetrakis(N-methylpyridinium-3-yl)porphyrin, TMePyP), and gold nanorods (AuNRs) anchored on graphene-oxide (GO) sheet. The TMePyP was initially synthesized by Adler method, followed by methylation, while GO and AuNRs were synthesized using Hummer's and seed-mediated methods, respectively. The structural and optical properties of TMePyP were confirmed using UV-Vis, zeta analyzer, PL, FTIR and NMR. The formation of both GO and AuNRs was confirmed by UV-Vis-NIR, FTIR, TEM and zeta analyzer. TMePyP and AuNRs were anchored on GO to form GO@AuNRs-TMePyP nanocomposite. The as-synthesized nanocomposite was stable in RPMI and PBS medium, and, on irradiation, produced high heat than the bare AuNRs, with high photothermal efficiency. In addition, the nanocomposite produced higher singlet oxygen than TMePyP with high biocompatibility in the absence of light. These results indicated that the as-synthesized nanocomposite is a promising dual photodynamic and photothermal agent for cancer therapy.